Evaluation of the Cipalabuan River's water quality and measures for reducing water pollution in the Sukabumi Regency - Rachmawati, Annis; Priatna, Dolly; Rosadi, Rosadi (Universitas Pakuan, 2024)
The Cipalabuan River serves as an ecosystem that provides habitat for many species and as a source of water for industry, agriculture, and drinking. However, growing industrial and residential activity poses a threat to the amount and quality of river water. The river has recently contributed to both liquid and solid waste, which has lowered the quality of the river's water. The Cipalabuan River flows through the city center from upstream to downstream, collecting pollutants from the discharge of local activities along the river's course, including liquid and solid waste. By monitoring and computing the water's quality at a certain location and time, this study seeks to ascertain the current state of water quality. In order to create a sequential explanatory design, a mixed method approach was used, mixing quantitative and qualitative methodologies in parallel. Water quality in the Cipalabuan River is influenced by a number of factors, including the actions of those who use the river as a disposal site, public ignorance of the need to control pollution, competing interests in the management of water resources, and a lack of cooperation between authorized agencies in the management of natural resources and the control of water pollution. ABSTRAK Sungai Cipalabuan berfungsi sebagai ekosistem yang menyediakan habitat bagi banyak spesies dan sebagai sumber air untuk industri, pertanian, dan minum. Namun, meningkatnya aktivitas industri dan pemukiman menimbulkan ancaman terhadap kuantitas dan kualitas air sungai. Akhir-akhir ini sungai tersebut menghasilkan limbah cair dan padat sehingga menurunkan kualitas air sungai. Sungai Cipalabuan yang mengalir melalui pusat kota dari hulu ke hilir mengumpulkan zat-zat pencemar yang berasal dari buangan aktivitas masyarakat di sepanjang aliran sungai, termasuk limbah cair dan padat. Dengan memantau dan menghitung kualitas air pada lokasi dan waktu tertentu, penelitian ini berupaya mengetahui kondisi kualitas air saat ini. Untuk membuat desain penjelasan sekuensial, pendekatan metode campuran digunakan, yang memadukan metodologi kuantitatif dan kualitatif secara paralel. Kualitas air di Sungai Cipalabuan dipengaruhi oleh beberapa faktor, antara lain tindakan pihak yang memanfaatkan sungai sebagai tempat pembuangan sampah, ketidaktahuan masyarakat akan perlunya pengendalian pencemaran, persaingan kepentingan dalam pengelolaan sumber daya air, dan kurangnya sumber daya manusia. kerjasama antar instansi yang berwenang dalam pengelolaan sumber daya alam dan pengendalian pencemaran air.